2021
DOI: 10.1155/2021/5070099
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Validation of a Novel Mitophagy-Related Gene Prognostic Signature for Hepatocellular Carcinoma Based on Immunoscore Classification of Tumor

Abstract: Emerging evidence suggested that mitophagy may play an important role in the progression of hepatocellular carcinoma (HCC), whereas the association between mitophagy-related genes and HCC patients’ prognosis remains unknown. In this study, we aimed to investigate the potential prognostic values of mitophagy-related genes (MRGs) on HCC patients at the genetic level. According to median immunoscore, we categorized HCC patients from TCGA cohort into two immune score groups, while 39 differential expression MRGs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…As clearly illustrated by Bru-seq trace diagrams (Figure ), QN523 increases the transcription of select autophagy-related genes WIPI1 (12.8-fold, Figure A), FAM129A (16.8-fold, Figure B), homocysteine-inducible ER protein with ubiquitin like domain 1 (HERPUD1) (9.8-fold, Figure C), GABARAPL1 (7.8-fold, Figure D), HMOX1 (13-fold, Figure E), and MAP1LC3B (6.8-fold, Figure F). WIPI1, GABARAPL1, and MAP1LC3B are well-established autophagy-related genes and relevant cancer markers at both gene and protein levels. HERPUD1 is a part of the ER-associated degradation machinery involved in ubiquitin-dependent degradation of misfolded proteins in the ER . FAM129A an ATF4 target genes plays a direct role in autophagy. , Heme oxygenase (HMOX1) acts as a cytoprotective gene against several forms of cell death including autophagy .…”
Section: Results and Discussionmentioning
confidence: 99%
“…As clearly illustrated by Bru-seq trace diagrams (Figure ), QN523 increases the transcription of select autophagy-related genes WIPI1 (12.8-fold, Figure A), FAM129A (16.8-fold, Figure B), homocysteine-inducible ER protein with ubiquitin like domain 1 (HERPUD1) (9.8-fold, Figure C), GABARAPL1 (7.8-fold, Figure D), HMOX1 (13-fold, Figure E), and MAP1LC3B (6.8-fold, Figure F). WIPI1, GABARAPL1, and MAP1LC3B are well-established autophagy-related genes and relevant cancer markers at both gene and protein levels. HERPUD1 is a part of the ER-associated degradation machinery involved in ubiquitin-dependent degradation of misfolded proteins in the ER . FAM129A an ATF4 target genes plays a direct role in autophagy. , Heme oxygenase (HMOX1) acts as a cytoprotective gene against several forms of cell death including autophagy .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Mitophagy as a selective degradation process, is critical to keeping mitochondria healthy, producing ATP, and maintaining neuronal activity and survival by removing impaired mitochondria. MRGs have been previously reported as prognostic or diagnostic markers for various tumors, including pancreatic cancer ( Zhuo et al, 2022 ), breast cancer ( Zhao et al, 2022 ), and liver cancer ( Chen et al, 2021 ; Xu et al, 2022 ), whereas only a limited number of studies have examined the usefulness of them as AD biomarkers. Pakpian et al (2020) recently reported that alterations in mitochondrial dynamic-related genes in the peripheral blood may be useful for diagnosing AD.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al used 16 survival MRGs to construct the prognosis model [ 65 ]. Chen et al categorized patients into two groups according to the median immune score and searched the MRGs between the groups to construct the prognosis model, but they did not construct mitophagy-related HCC subtypes [ 66 ]. Wang et al identified HCC subtypes based on 26 selection-free MRGs, while our study identified the low-risk C1 subtype and high-risk C2 subtype based on 21 survival-related MRGs [ 67 ].…”
Section: Discussionmentioning
confidence: 99%